International meta-analysis of 684, 660 men with vasectomies: a study utilising the International Population Data Linkage Network. (2018) - Randall, Sean; Boyd, James; Fuller, Emma; Brooks, Caroline; Morris, Carole; Earle, Craig; Ferrante, Anna; Moorin, Rachael; Semmens, James; Holman, D'Arcy
No abstract available